Reflection of the Test-Item Quality in State SMP and SMA in Bandar Lampung - Ujang Suparman (Aksara: Jurnal Bahasa dan Sastra, 2019)
The objectives of this research are to analyze critically the quality of test items used in SMP and SMA (mid semester, final semester, and National Examination Practice) in terms of reliability as a whole, level of difficulty, discriminating power, the quality of answer keys and distractors. The methods used to analyze the test items are item analysis (ITEMAN), two types of descriptive statistics for analyzing test items and another for analyzing the options. The findings of the research are very far from what is believed, that is, the quality of majority of test items as well as key answers and distractors are unsatisfactory. Based the results of the analysis, conclusions are drawn and recommendations are put forward. http://dx.doi.org/10.23960/aksara/v20i2.pp72-87